FOOD RESOURCE SHARING AMONG BENTHIC AND NEKTONIC STREAM FISH SPECIES - Guilherme Raphael Camargo Arcanjo SILVA; Maurício CETRA (Boletim do Instituto de Pesca)
Several tropical freshwater fish species are generally generalistic feeders, sometimes followed by a diet reduction during the period of decreased resource availability. This study aimed to analyze the dietary overlap between nektonic and benthic fish species. The stomachs of 82 obligatory nektonics and 52 benthic were removed. The diet composition for each individual was determined based on the analysis of the stomach content, and the contents were grouped into 11 categories. For the analysis of food items, the method of degree of food preference was used. To verify the niche overlap between benthic and nectonic, the Pianka index was applied. Benthic species consumed items across all 11 food categories and nektonic species consumed nine. The diet composition of species with nektonic and benthic habits showed a significant difference. Dietary overlapping suggests a supply of the same resources, as they are shared by both groups. The high concentration of water insect larvae in the food content of all sampled fish species, regardless of the position in the water column, shows the importance of insects in the water ecosystems. The composition of ecosystem diets is helpful towards understanding the community structure and can explain the coexistence between different fish’s groups where live in different micro-habitats and how tactics used to capture food which may minimize the effects of overlapping and competitive exclusion.